MANUSIA DALAM PANDANGAN YAHUDI - Agus Darmaji (Religi: Jurnal Studi Agama-agama, 2015)
This paper is divided into three sections. First, it gives a brief  introductory of the Jews. Second, it explains the process of  the creation of  human. Third, it elaborates the basis of  human behavior in the Jewish, like morality, suffering , and the ‘chosen people.’ In terms of  the creation of  human beings, Judaism states that human is made of the dust which is then fulfilled by the spirit through his nose. Human is created in God’s image. It is not only his soul, but also his body, represents the symbol of  God. The Hebrew Bible (Holy Book), in general, vastly embraces the doctrines of morality that should be used as the basis of  the behavior of  the Jews. This is particularly apparent from the teachings contained in the Ten Commandments. In addition, it also considers the chosen people as a liability, rather than an opportunity to obtain particular privileges; thus, they were elected to serve God and to undergo several sufferings in implementing the service.